DINAMIKA PSIKOLOGIS REMAJA GAY DALAM KASUS VIRAL VIDEO SEKSUAL: STUDI KASUS DENGAN LATAR BELAKANG KURANGNYA KASIH SAYANG AYAH - Susanti, Dahlia; Hayati, Nandie (Ensiklopedia Education Review, 2025)
Abstract: This study examines the psychological and social dynamics experienced by an 18-year-old male adolescent who identifies as gay and has engaged in same-sex sexual activity. The case began with a lack of paternal affection, which triggered the subject’s involvement in the LGBT community and sexual behavior. The virality of a video showing the subject’s sexual activity on social media caused psychological pressure, stigma, and social isolation. A qualitative case study method was used, involving in-depth interviews and non-participatory observation. The results show that emotional neglect within the family contributes to behavioral patterns, and the viral video worsens the subject’s psychosocial condition. The study recommends the need for psychosocial support and education for families and society to reduce stigma.Keywords: psychological dynamics of gay adolescents, viral video, lack of paternal affection.